2020
DOI: 10.18805/ijare.a-5521
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Study on IAA production by Bradyrhizobium japonicum and Bacillus subtilis and Its Effect on Vigna radiata Plant Growth

Abstract: Background: The use of chemical fertilizers and pesticides raises concerns about environmental pollution, health hazards and the destruction of biotic groups that support plant growth. Plant growth-promoting rhizobacteria (PGPR) thrive in the rhizosphere of plants are the auspicious alternative for these chemicals. PGPR plays a critical role in plant growth and development, along with biocontrol activities. Methods: In this present study, two effective microbes, Bradyrhizobium japonicum and Bacillus subtilis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…High auxin production potential was also recorded in the PGPR B. subtilis (Mt3b) isolated from rhizosphere of Malvastrum tricuspidatum ( Wagi and Ahmed, 2019 ). A recent comprehensive study by Kiruthika and Arunkumar (2020) showed that B. subtilis had the potential to produce IAA and subsequently ICA, resulting in improved root and shoot length as well as dry weight and overall plant growth. Additionally, Paenibacillus species have been reported to produce IAA in contribution to plant growth ( Xu and Kim, 2014 ; Grady et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…High auxin production potential was also recorded in the PGPR B. subtilis (Mt3b) isolated from rhizosphere of Malvastrum tricuspidatum ( Wagi and Ahmed, 2019 ). A recent comprehensive study by Kiruthika and Arunkumar (2020) showed that B. subtilis had the potential to produce IAA and subsequently ICA, resulting in improved root and shoot length as well as dry weight and overall plant growth. Additionally, Paenibacillus species have been reported to produce IAA in contribution to plant growth ( Xu and Kim, 2014 ; Grady et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“… Devi et al (2022) also demonstrated that inoculation of P. extremorientalis increased the plant growth parameters such as fresh weight, dry weight, shoot length and root length of chili. Similarly, Kiruthika and Arunkumar (2021) also demonstrated that inoculation of B. japonicum increased fresh and dry weight of mungbean. Miljaković et al (2022) also reported that inoculation of B. japonicum improved growth parameters of soybean.…”
Section: Resultsmentioning
confidence: 76%
“…Bacillus species perform dual functions by showing antagonism against plant pathogens and displaying plant growth promoting properties, which could be highly advantageous in developing the best possible inoculants for soybean, especially if applied in combination with the symbiotic bacteria. Recently, a beneficial effect of Bacillus subtilis and Bradyrhizobium japonicumon plant growth was reported by Kiruthika and Arunkumar (2020), probably due to the IAA production, P-solubilization and siderophore production. Similarly, Singh and Singh (2018) observed that co-inoculation with PGPR and rhizobia is a promising strategy for the enhancement of plant absorption of P, as well as plant growth and grain yield.…”
Section: Resultsmentioning
confidence: 99%